THE ROLE OF PSYCHOLOGY IN LEARNING LANGUAGES - Xodjayorova Sayora Abdullayevna; Samatullayeva Lobar Sherzod qizi (Journals Park Publishing, 2023)
Language is the way to explore new knowledge, culture and people. Regarding the fact that it is connected strongly sociology and psychology what helps to boost the general development of humanism. This article illustrates some key connections of learning languages with psychology and the way close chain of languages with other essential humanitarian fields. Furthermore, language teachers' training collaborated with not only pedagogy, but also young learner’s psychology needs a deep research in today's world that is becoming more than easy to lose the interest of students for classes.
Keywords: Psychology, limiting beliefs, empowering beliefs, English trauma, motivation, brain, incantation, emotion, non - linguistic factors.